Sodium intake and dietary sources of sodium in undergraduate students from Novi Sad, Serbia - Jovičić-Bata Jelena; Grujičić Maja; Rađen Slavica; Novaković Budimka (Vojnosanitetski Pregled)
Background/Aim. Data on sodium intake and sources of sodium in the diet in Serbia are limited. The aim of this study was to estimate the sodium intake and identify the sources of sodium in the diet of undergraduate students attending the University of Novi Sad. Methods. Students completed a questionnaire to gather data on their gender, age and university faculty attended, and then a 24 h dietary recall. The sodium intake of the students was calculated using the dietary recall data and data on the sodium content of foods. The contribution of different food groups as well as of specific foodstuffs to the total sodium intake was calculated. Results. The mean estimated sodium intake of the students was 3,938.5 ± 1,708.1 mg/day. The sodium intake of 89.1% of the surveyed students exceeded the guideline for sodium intake, the majority of the sodium coming from processed foods (78.9% of the total sodium intake). The food groups that contributed the most to the total sodium intake of the students were meat and meat products (21.7%) and cereals and cereal-based products (18.6%). Bread and other bakery products were responsible for 13.1% of the total sodium intake. Conclusion. High sodium intake in students of the University of Novi Sad puts them at high risk of developing high blood pressure. The food industry should work towards reformulating products with high sodium content, especially bread and other bakery products. Efforts should be taken to reduce sodium intake among undergraduate students in Novi Sad.